Evaluation And Performance Check For Packet Characteristics By Pervasive OSI Model Metrics - SHRIDEVI SALI (2008)
INTERNAL GUIDE : Anirban Basu . EXTERNAL GUIDE : Shashank Parashar USN No : 1MJ07SCS13 CARRIED OUT AT : CBK Infotech India (P) Ltd Bangalore ACC NO : PC66
Keywords: M.Tech Computer Science